2016
DOI: 10.1016/j.jmbbm.2015.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Origin of ultralow Young׳s modulus in a metastable β-type Ti–33Nb–4Sn alloy

Abstract: Although there is difficulty in growing a Ti-33Nb-4Sn single crystal due to its ultralow β-phase stability, the single-crystal elastic constants of metastable β-type Ti-33Nb-4Sn (wt%) alloy were extracted successfully from its polycrystal by in-situ synchrotron X-ray diffraction technique, to clarify the origin of the ultralow Young's modulus in its polycrystal. It is indicated that compared to binary TiCr, TiV and TiNb alloys, the Ti-33Nb-4Sn alloy possesses slightly lower β-phase stability with respect to {1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Further investigation shows that this ultralow modulus is closely associated with its low β-phase stability with respect to α" martensitic transformation [30]. It is also shown that the Ti-33Nb-4Sn alloy exhibits multiple deformation behavior, involving "double yielding", nonlinear deformation and conventional linear elastic deformation, under different thermo-mechanical treatment conditions [29,30].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Further investigation shows that this ultralow modulus is closely associated with its low β-phase stability with respect to α" martensitic transformation [30]. It is also shown that the Ti-33Nb-4Sn alloy exhibits multiple deformation behavior, involving "double yielding", nonlinear deformation and conventional linear elastic deformation, under different thermo-mechanical treatment conditions [29,30].…”
Section: Introductionmentioning
confidence: 88%
“…Further investigation shows that this ultralow modulus is closely associated with its low β-phase stability with respect to α" martensitic transformation [30]. It is also shown that the Ti-33Nb-4Sn alloy exhibits multiple deformation behavior, involving "double yielding", nonlinear deformation and conventional linear elastic deformation, under different thermo-mechanical treatment conditions [29,30]. However, the deformation behaviour of the Ti-33Nb-4Sn alloy, especially its correlation with SIM transformation, has not yet been investigated detailedly, although an in-depth understanding of this issue might help to establish theoretical foundations for designing novel biomedical Ti alloys with ultralow elastic modulus.…”
Section: Introductionmentioning
confidence: 93%
“…However, the alloys may suffer from biomechanical incompatibility. There is a difference between the elastic modulus of the material (ca 105 GPa) and the modulus of bone (16)(17)(18)(19)(20)(21)(22)(23)(24)(25) GPa for cortical and 1-4 GPa for trabecular bone) [3]. This difference may cause the loss of mechanical bond because the regeneration of the bone tissue is probably controlled via mechanical stimulation of osteocytes [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…This structure reduces tensile strength, fatigue strength and hardness [19][20][21]. However, the presence of alpha and omega phases can be suppressed by tin alloying, and the Young moduli of these alloys are about 40 GPa [16,[22][23][24][25][26]. Tin and other elements, such as Nb and Ta, also improve the corrosion resistance by enriching the passive layer by stable and non-toxic oxides such as Nb 2 O 5 , Ta 2 O 5 , and SnO 2 [16,[27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that the ultralow modulus of Ti-33Nb-4Sn (wt. %) alloy is closely related to its low β-phase stability with respect to α" martensitic transformation [13]. However, the martensitic transformation behaviour in the Ti-33Nb-4Sn alloy has not yet been clarified in detail, although an in-depth understanding of this issue may provide help in establishing foundations for developing new Ti alloys, such as biomedical Ti alloy with ultralow elastic modulus.…”
Section: Introductionmentioning
confidence: 99%